The Holocene humid period in the Nefud Desert: Hunters and herders in the Jebel Oraf palaeolake basin, Saudi Arabia. (July 2020) - Guagnin, Maria; Breeze, Paul; Shipton, Ceri; Ott, Florian; Stewart, Mathew; Bateman, Mark; Martin, Louise; Graham, Lisa; el-Dossary, Sarah; Kingwell-Banham, Eleanor; Zahrani, Badr; al-Omari, Abdulaziz; et al.
Abstract: Archaeological surveys and excavations in the Jebel Oraf palaeolake basin, north-western Saudi Arabia, have identified a well-preserved early- to mid-Holocene landscape. Two types of occupation site can be distinguished: nine small and ephemeral scatters from single occupation phases on the slopes of sand dunes and three hearth sites indicative of repeated occupation on palaeolake shorelines. In addition, 245 rock art panels, 81 cairns, and 15 stone structures were recorded. This diverse dataset provides an opportunity to reconstruct occupation patterns and changes in landscape use. A particularly important site, Jebel Oraf 2, documents two episodes of lake high stands at ca. 6500 BC and 5300 BC, flooding parts of the locality. Neolithic pastoralists likely occupied the site after the end of the wet season, when the terrain was dry. Earlier sites are located in dune embayments some 7–14 m above the shore of the palaeolake. These locations are consistent with hunting strategies identifiable in the rock art that suggest wildlife was ambushed at watering places. Later rock art at Jebel Oraf also documents the hunting of wild camel in the Iron Age. The lithic industries documented in the Jebel Oraf basin support arguments of repeated contact with Levantine populations. Highlights: Well preserved Neolithic landscape in the Nefud Desert of northern Saudi Arabia. Evidence for changes in landscape use across the transition to herding. Two lake high stands show seasonal use of the area by early pastoralists. Rock art documents the presence of wild camel in the Iron Age. Lithic industry indicative of contacts with the Levant over several millennia.